Pengembangan LKPD Berbasis Aktivitas pada Mata Pelajaran IPS Materi Sumber Daya Alam Kelas IV SD - Niawati, Darma; Sujarwo, Sujarwo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The development of science and technology should be developed to facilitate the student learning process. In the learning process, an instrument is needed that can make it easier for students to learn and can increase learning activities, one of which can use student worksheets (LKPD). The purpose of this study was to develop LKPD for natural resources for class IV SD. The form of this research is R&D (Research and Development) and this development model uses the ADDIE model which consists of several stages. 1.Analysis, 2. Design, 3. Development. Data collection through observation, product design using the Canva application. The LKPD assessment was validated by media and material experts, namely two lecturers at the Muslim Nusantara University AlWashliyah Medan. The results of the assessment from the validation stage are used as material in revising the LKPD. Based on the results of this study, it can be concluded that social studies learning using LKPD can help in the teaching and learning process of fourth grade elementary school students, this is evident from the results of the validation of media experts who received appropriate responses to use after revision while material expert validation received appropriate responses to use with the material.